Early Christian Educational Institutions in Shaanxi: Their Educational Philosophy and Influence—Taking the “Zunde Academy,” Predecessor of Xi’an No. 3 Middle School, as an Example - WANG Shuofeng (Journal of Research for Christianity in China (JRCC), 2025)
Protestant Christianity played a pivotal role in modern Chinese education. Beyond establishing schools and other educational institutions, it diverged significantly from traditional Chinese education in multiple aspects, including target audiences, educational philosophies, teaching methodologies, administrative systems, and curriculum content. This paper traces the historical entry of Protestantism into Shaanxi. Drawing upon extensive historical archives and cultural-historical materials, it compiles for the first time a comprehensive list of all schools established by Christian missionaries in Shaanxi from the late 19th to early 20th centuries. Using the example of the first Western-style school in Xi’an—the Zun De Academy (present-day Xi’an No. 3 Middle School)—it examines the educational philosophies of early Christian schools in Shaanxi and their profound impact on modern education in the province.